Characterisation of parasympathetic ascending nerves in human colon - Johnson, Michaela E.; Humenick, Adam; Peterson, Rochelle A.; Costa, Marcello; Wattchow, David A.; Sia, Tiong Cheng; Dinning, Phil G.; Brookes, Simon J. H. (Frontiers in Neuroscience, 2022)
Background: In the human large bowel, sacral parasympathetic nerves arise from S2-S4, project to the pelvic plexus ("hypogastric plexus") and have post-ganglionic axons entering the large bowel near the rectosigmoid junction. They then run long distances orally or aborally within the bowel wall forming "ascending nerves" or "shunt fascicles" running in the plane of the myenteric plexus. They form bundles of nerve fibres that can be distinguished from the myenteric plexus by their straight orientation, tendency not to merge with myenteric ganglia and greater width. Aim: To identify reliable marker(s) to distinguish these bundles of ascending nerves from other extrinsic and intrinsic nerves in human colon. Methods: Human colonic segments were obtained with informed consent, from adult patients undergoing elective surgery (n=21). Multi-layer immunohistochemical labelling with neurofilament-H (NF200), myelin basic protein (MBP), von Willebrand factor (vWF) and glucose transporter 1 (GLUT1), and rapid anterograde tracing with biotinamide, were used to compare ascending nerves and lumbar colonic nerves. Results: The rectosigmoid and rectal specimens had 6-11 ascending nerves spaced around their circumference. Distal colon specimens typically had 1-3 ascending nerves, with one located near the mesenteric taenia coli. No ascending nerves were observed in ascending colon specimens. GLUT1 antisera labelled both sympathetic lumbar colonic nerves and ascending nerves in the gut wall. Lumbar colonic nerves joined the myenteric plexus and quickly lost GLUT1 labelling, whereas GLUT1 staining labelled parasympathetic ascending nerves over many centimetres. Conclusion: Ascending nerves can be distinguished in the colorectum of humans using GLUT1 labelling combined with NF200.